A Predictive Model of Postnatal Surgical Intervention in Children With Prenatally Detected Congenital Anomalies of the Kidney and Urinary Tract - Vasconcelos, Mariana A.; Oliveira, Eduardo A.; Simões e Silva, Ana Cristina; Dias, Cristiane S.; Mak, Robert H.; Fonseca, Carolina C.; Campos, Ana Paula M.; Steyerberg, Ewout W.; Vergouwe, Yvonne (Frontiers in Pediatrics, 2019)
The aim of this study was to identify predictive factors of the need of surgery and to develop a model to assess individualized risk of surgical intervention in patients with antenatal hydronephrosis. This is a retrospective cohort study of 694 infants with prenatally detected congenital anomalies of kidney and urinary tract with a median follow-up time of 37 months. The main event of interest was the need for surgical intervention. A predictive model was developed using Cox model with internal validation by bootstrap technique. Of 694 patients, 164 (24%) infants needed surgical intervention in a median age of 7.8 months. Predictors of the need of surgery in the model were: baseline glomerular filtration rate, associated hydronephrosis, renal damage, renal pelvic dilatation severity, and period of admission. The optimism corrected c statistic for the model was 0.84 (95%CI, 0.82-0.87). The predictive model may contribute to identify infants at high risk for surgical intervention. Further studies are necessary to validate the model in patients from other settings.